Disaster management of Malaka district government in flood disaster management - Yulius N. Bria; Laurensius P. Sayrani; Nursalam Nursalam (Annals of Management and Organization Research, 2020)
Purpose: This study aimed to analyze the disaster management of the Malaka Regency Government in flood disaster management. Research methodology: The research method used in this study is a qualitative research method. The informants in this study were elements of the government as well as elements of society consisting of the Flood Victims Community. The analysis technique in this study uses data analysis developed by Miles and Huberman (2014: 10) as follows; (a) data reduction (b) data display and (c) concluding. Finding: The result of this research is that the Malaka Regency Government's disaster management in flood disaster management has implemented the best management even though it is still not optimal. Limitations: This study's limitation is that this study only discusses the disaster management of the Malaka district government in overcoming the floods that occurred there. Contribution: This research becomes scientific information for public administration and disaster management. Keywords: Management, Disaster, Government